Becoming a missional church: the struggle of the Lesotho Evangelical Church in Southern Africa or Paris Evangelical Missionary Society in Meadowlands, Soweto - Kganyapa, Leonard T.; Kgatla, Selaelo T. (HTS Teologiese Studies / Theological Studies, 2016)
The existence of the Lesotho Evangelical Church in Southern Africa (LECSA) and Paris Evangelical Missionary Society (PEMS) in the western areas of Johannesburg, South Western Township (Soweto) and, more poignantly, Meadowlands and their forced removal experience are succinctly captured. The struggle of the LECSA and PEMS Meadowlands Parish in becoming a missional ecclesia in a sea of missional challenges in her context is vividly spelt out. They, inter alia, include constitutional matters, language policy, finances, ministerial preparation, lay-ministry development, institutionalisation of ministry, unity issues, prophetic ministry, mission and evangelism. The researcher, then, proposes an intervention – of course not a perfect one – that perhaps will galvanise the LECSA and PEMS Meadowlands Parish members to improve on what they have been doing and become a missional ecclesia in her context, Meadowlands.
free
Keywords: Church and community – Case studies; Clergy – Education; Eviction; Institutionalism (Religion); Language question in the church; Lay ministry; Lesotho Evangelical Church in Southern Africa; Missions – Theory; Open access; Peer reviewed; Politics and Christianity – Reformed churches; Prophetic office; Société des missions évangéliques de Paris; South Africa – Socio-economic conditions; Soweto (South Africa)